Letter (copy) : Basque Children's Committee - Tewson, Vincent
038-0042-001 Secretary's HVT/FC/EK/878. 9th April, 1940. The Duchess of Atholl, Eastwood, DUNKELD, Perthshire. BASQUE CHILDREN'S COMMITTEE. Miss Rathbone has sent on to me your letter of the 6th April. I entirely concur with the main points of your letter. In regard to the financial position, I quite agree that it is desperate, but I am equally convinced that it will be just as desperate in six months time. Miss Rathbone is, however, consulting me in regard to a date for a meeting of the Basque Children's Committee, when I hope the position will be thoroughly gone into. I wonder if there is any chance of your being present. 292/946/38/42